2016
DOI: 10.1007/bf03379738
|View full text |Cite
|
Sign up to set email alerts
|

Synesthetic Associations and Psychopathological Symptoms: Preliminary Evidence in Young Women

Abstract: Synesthesia is a neuropsychological condition in which stimulation of one sensory modality or cognitive pathway is associated with unusual experiences in a different unstimulated modality. In this context a purpose of this study is to find relationships between word-color associations and psychopathological symptoms of anxiety (SAS), depression (BDI-II), alexithymia (TAS-20) and symptoms of traumatic stress (TSC-40) in 43 healthy young women (mean age 18.25). Results of this study show that colors associated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Differences in nonverbal emotional expression at the level of body posture and facial expression are seen in ASD, with evidence of abnormalities in emotional facial expression which may be explained by co-occurring alexithymia ( Trevisan et al, 2016 ). Art allows individuals with alexithymia to express themselves and potentially access the verbal expression system which they need to process and vent their emotions ( Meijer-Degen and Lansen, 2006 ); interestingly, individuals with ASD have high rates of synesthesia and often use colors to express their emotions ( Neckar and Bob, 2017 ). Dance, or rhythmic movement therapy, is another effective outlet for symptoms of alexithymia ( Malkina-Pykh, 2013 ) and may be intricately linked to emotional competence ( Bojner Horwitz et al, 2015 ).…”
Section: Mechanistic Links In Emotional Processing Between Alexithymimentioning
confidence: 99%
“…Differences in nonverbal emotional expression at the level of body posture and facial expression are seen in ASD, with evidence of abnormalities in emotional facial expression which may be explained by co-occurring alexithymia ( Trevisan et al, 2016 ). Art allows individuals with alexithymia to express themselves and potentially access the verbal expression system which they need to process and vent their emotions ( Meijer-Degen and Lansen, 2006 ); interestingly, individuals with ASD have high rates of synesthesia and often use colors to express their emotions ( Neckar and Bob, 2017 ). Dance, or rhythmic movement therapy, is another effective outlet for symptoms of alexithymia ( Malkina-Pykh, 2013 ) and may be intricately linked to emotional competence ( Bojner Horwitz et al, 2015 ).…”
Section: Mechanistic Links In Emotional Processing Between Alexithymimentioning
confidence: 99%
“…Through experiments, Neckar and Bop found that word color associations are closely related to psychopathological symptoms such as anxiety, depression, mental retardation, and traumatic stress symptoms. Experiments have shown that this is caused by an abnormal experience in another unstimulated way caused by stimulation of one sensory or cognitive pathway [11]. To put it simply, it is a neuropsychological disease caused by synesthesia, just like what people call "the wrong line of nerves."…”
Section: Introductionmentioning
confidence: 99%